Factors Influencing Malay Language Learning among Malaysian Chinese Independent Secondary School Students - Chew, Fong Peng (Jurnal Arbitrer, 2025)
The Malaysian Chinese Independent Secondary Schools (MCISS) strive to develop students proficient in three languages: Chinese, English, and Malay. Despite the national status of the Malay language, learners in these schools consistently demonstrate low proficiency in it. A key reason for this shortfall is the students’ limited interest in learning the language. This study explores the underlying factors contributing to this phenomenon, including students’ attitudes toward the language, motivation, instructional methods, learning strategies, family engagement, National Education Policy and UEC recognition. Employing a quantitative survey design, data were collected from 4,602 Senior II MCISS students through convenience sampling. Pearson correlation analysis indicated positive relationships between language learning interest and variables such as language attitude, motivation, instructional methods, learning strategies, family engagement, and National Education Policy and UEC recognition. Multiple regression analysis revealed that motivation, attitude, classroom learning, family engagement, the National Education Policy, and UEC recognition collectively accounted for 32.2% of the variance in students’ interest in learning Malay. The study’s implications extend to policymakers, educators, and curriculum designers, suggesting the integration of culturally relevant and engaging teaching strategies, stronger home–school partnerships, and policy adjustments to strengthen Malay language learning motivation among MCISS students.